Contribution of the Mitochondrial Carbonic Anhydrase (MoCA1) to Conidiogenesis and Pathogenesis in Magnaporthe oryzae - Dang, Yuejia; Wei, Yi; Batool, Wajjiha; Sun, Xicen; Li, Xiaoqian; Zhang, Shi-Hong (Frontiers in Microbiology, 2022)
The interconversion of CO2 and HCO3− catalyzed by carbonic anhydrases (CAs) is a fundamental biochemical process in organisms. During mammalian-pathogen interaction, both host and pathogen CAs play vital roles in resistance and pathogenesis; during planta-pathogen interaction, however, plant CAs function in host resistance but whether pathogen CAs are involved in pathogenesis is unknown. Here, we biologically characterized the Magnaporthe oryzae CA (MoCA1). Through detecting the DsRED-tagged proteins, we observed the fusion MoCA1 in the mitochondria of M. oryzae. Together with the measurement of CA activity, we confirmed that MoCA1 is a mitochondrial zinc-binding CA. MoCA1 expression, upregulated with H2O2 or NaHCO3 treatment, also showed a drastic upregulation during conidiogenesis and pathogenesis. When MoCA1 was deleted, the mutant ΔMoCA1 was defective in conidiophore development and pathogenicity. DAB staining indicated that more H2O2 accumulated in ΔMoCA1; accordingly, ATPase genes were down-regulated and ATP content decreased in ΔMoCA1. Summarily, our data proved the involvement of the mitochondrial MoCA1 in conidiogenesis and pathogenesis in the rice blast fungus. Considering the previously reported HCO3− transporter MoAE4, we propose that MoCA1 in cooperation with MoAE4 constitutes a HCO3− homeostasis-mediated disease pathway, in which MoCA1 and MoAE4 can be a drug target for disease control.